THE EFFECT OF FINANCIAL LEVERAGE ON THE ISLAMIC BANKS’ PERFORMANCE IN ASIAN COUNTRIES - Rahim, Abdul; Ashraf, Shagufta; Iftikhar, Waqas; Khan, Dr. Muhammad Muddassar; Mehmood, Shahid; Siddique, Dr. Muhammad (The journal of contemporary issues in business and government, 2021)
The current research is designed for analyzing the impact of the financial leverage on performance of the Islamic Banks in the countries of Asian region. The research study comprises of the population of Islamic Banks from Asian region. The data of twenty five Islamic banks from Asian economies for the time period (2010 -2019) is used, and this data have been retrieved from the Thomson Reuters Data Stream. Researcher has used latest version of E-views for analyzing the data of current study. Data analyses are performed by applying the tests like Descriptive Statistics, Correlation Analysis, Common Effect Model, Fixed Effect Model, Likelihood Test, Random effect Model and Hausman Test. Current study used the fixed effect regression model. Findings of current study showed significant and positive impact of Leverage on Islamic Banks performance in Asian Region. In the light of results and findings it is analyzed that financial leverage has positive and significant association for ROA in the presence of control variables (Bank Size and Bank Efficiency).It is clear indication from findings that the high financial leverage increases the performance of Islamic banks in Asian countries. The result of the research study is not having supporting the Agency Cost Theory. According to Agency Cost Theory when there is increase in the equity of banks this will have negative outcomes for firm value. The results of current research work are providing strong evidence in support of the Signaling Theory. Signaling theory describes that if there is higher capital then the performance of the banks will be much better. The findings revealed that financial leverage is on the level in Islamic Banks that totally depends upon the flexibility ratio for the adjustment of the value of debt and their power of earning.